1986
DOI: 10.1111/j.1399-0004.1986.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Usher syndrome in four Norwegian counties

Abstract: Among 89 probands selected for tapeto‐retinal degeneration, 18 (20%) were given the diagnosis of Usher syndrome. Among the relatives of the probands another 10 cases of Usher syndrome were found. The distribution on type diagnoses was: Usher syndrome type I: 14 cases, type II: 10 cases and type III: four cases. The pattern of inheritance was autosomal recessive for 12 families, and the remaining six probands were solitary cases without consanguinity between the parents. There was a high intrafamiliar correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…The types of disorders observed were not uniform and included atypical autism, mental retardation, schizophrenia, and conduct disorder. The number of individuals found with schizophrenia in this study (1 child) is congruent with results reported by Nuutila [15] and Grøndahl and Mjøen [14] using samples of 133 and 89 adults with Usher syndrome, respectively. Among the children without mental and behavioral disorders around one third was found to have psychosocial difficulties.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The types of disorders observed were not uniform and included atypical autism, mental retardation, schizophrenia, and conduct disorder. The number of individuals found with schizophrenia in this study (1 child) is congruent with results reported by Nuutila [15] and Grøndahl and Mjøen [14] using samples of 133 and 89 adults with Usher syndrome, respectively. Among the children without mental and behavioral disorders around one third was found to have psychosocial difficulties.…”
Section: Discussionsupporting
confidence: 91%
“…Schaefer and colleagues [40] found that the measured volume of the brain was significantly smaller compared to normal controls and Koizumi et al [10] found a global degeneration of the brain in one case with Usher syndrome and schizophrenia. Similar to the surveys by Nuutila [15] and Grøndahl and Mjøen [14] this study found that only some individuals with Usher syndrome had mental and behavioral disorders and the nomenclature of disorders was not uniform. Either different Usher genes are associated with different kinds of mental and behavioral disorders, or another explanation may be the necessary.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The prevalence has been estimated to be 3.5–16.6 in 100,000 (Boughman et al. ; Grondahl and Mjoen ; Rosenberg et al. ; Kimberling et al.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] USH type 1 (USH1) is characterized by congenital severe-toprofound HL and vestibular dysfunction; it is the second common type after USH type 2 and accounts for 25-44% of the USH cases. 7,11 Five causative genes have been identified: myosin VIIA (HUGO gene symbol MYO7A); Usher syndrome 1C, harmonin (USH1C); cadherinrelated 23 (CDH23); protocadherin-related 15 (PCDH15); and Usher syndrome 1G, Sans (USH1G). [12][13][14][15][16][17][18] Mutations in these genes have been observed in patients with USH1 from various ethnic origins, including Caucasian, African and Asian.…”
Section: Introductionmentioning
confidence: 99%